How do competing influences of selection history interact? A commentary on Luck et al. (2021). Issue 9 (21st October 2021) - Pearson, Daniel; Watson, Poppy; Le Pelley, Mike E.
ABSTRACT: Attention researchers have long debated the role that attentional control settings play in determining selection. In their article, Luck et al. (2021) have identified points of consensus among traditionally opposed models of attentional control, one of which is that prior experience (i.e., selection history ) allows attentional control settings to suppress attention to salient distractors by inhibiting the attentional priority of learned distractor features and/or locations. However, the influence of prior experience on attentional priority is not exclusively inhibitory. In particular, experiencing the relationship between a stimulus feature and reward has been shown to increase that feature's attentional priority. Here, we discuss recent findings investigating how these competing influences of selection history interact, suggesting that experience-driven distractor suppression and reward independently modulate attentional selection.